PENGEMBANGAN MEDIA KAKA BARA (KARTU KOSAKATA BAHASA ARAB) DALAM PEMBELAJARAN BAHASA ARAB DI TAMAN KANAK-KANAK KELOMPOK B: DEVELOPMENT OF KAKA BARA MEDIA (ARABIC VOCABULARY CARDS) IN ARABIC LANGUAGE LEARNING IN KINDERGARTEN GROUP B - Firmansyah Jihad (Universitas Negeri Semarang, 2024)
The main challenge in learning a second language is the lack of vocabulary. Choosing the right media is one of the most important factors in this regard. This article describes the development of innovative learning media, namely KAKA BARA (Arabic Vocabulary Cards) in learning Arabic in early childhood. The method used by researchers in this study is the RnD (research n development) method, using the ADDIE model approach and data collection techniques in the form of observation, interviews, tests, and documentation. KAKA BARA media is designed as vocabulary cards with attractive illustrations to help children learn Arabic vocabulary in a fun way. This design was produced through a needs analysis phase and validation from material experts and media experts. After going through the development stage, KAKA BARA media was validated by experts with an average score of 4 (good) for the material and language aspects, and a score of 5 (very good) for the design and graphics aspects. Several improvements were made based on expert suggestions, such as adding learning objectives, improving vocabulary writing, and adjusting colors. Based on the validation that has been carried out, KAKA BARA media is declared feasible to be implemented in Arabic vocabulary learning in kindergarten, especially for group B. This media is expected to improve students' mastery of Arabic vocabulary more effectively and attractively. This conclusion illustrates that the research objectives have been achieved by developing and validating learning media that are in accordance with the needs of students and teachers at Al Furqon Kindergarten, so that they can be used effectively in the Arabic vocabulary learning process.